2012
DOI: 10.1002/humu.22004
|View full text |Cite
|
Sign up to set email alerts
|

Non-USH2A mutations in USH2 patients

Abstract: We have systematically analyzed the two known minor genes involved in Usher syndrome type 2, DFNB31 and GPR98, for mutations in a cohort of 31 patients not linked to USH2A. PDZD7, an Usher syndrome type 2 (USH2) related gene, was analyzed when indicated. We found that mutations in GPR98 contribute significantly to USH2. We report 17 mutations in 10 individuals, doubling the number of GPR98 mutations reported to date. In contrast to mutations in usherin, the mutational spectrum of GPR98 predominantly results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 22 publications
3
49
0
1
Order By: Relevance
“…In addition, while many patients with Usher syndrome have significant vestibular dysfunction, 40 it is unclear whether patients with whirlin mutations (DFNB31 or Usher 2D) have vestibular deficits. 9,10,21,[41][42][43] None of the studies that reported on the phenotypes of these patients included detailed vestibular function tests. Therefore, additional studies are required to investigate the vestibular function in patients with whirlin mutations in order to gauge the potential therapeutic benefits of whirlin gene therapy on balance function in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while many patients with Usher syndrome have significant vestibular dysfunction, 40 it is unclear whether patients with whirlin mutations (DFNB31 or Usher 2D) have vestibular deficits. 9,10,21,[41][42][43] None of the studies that reported on the phenotypes of these patients included detailed vestibular function tests. Therefore, additional studies are required to investigate the vestibular function in patients with whirlin mutations in order to gauge the potential therapeutic benefits of whirlin gene therapy on balance function in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 35 patients had no function-affecting sequence variants identified before this investigation. The eight patients with two sequence variants in USH2A were included, as patients with three different function-affecting sequence variants located in two different genes 19,23 as well as patients with three different sequence variants located in the same gene, including USH2A, have been published previously. 15,24 The project was approved by the local ethics committee (H-3-2011-070) and carried out in accordance with the Declaration of Helsinki.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…[12][13][14] Function-affecting variants in PCDH15 may not only lead to USH1, but also to autosomal recessive nonsyndromic profound hearing impairment (DFNB23). 12 Most patients with USH2, including patients from Denmark, have function-affecting variants in USH2A, [15][16][17][18][19] which is located on chromosome 1. Sequence variants in USH2A are also responsible for atypical Usher syndrome and recessive nonsyndromic RP.…”
Section: Introductionmentioning
confidence: 99%
“…USH2 patients present with congenital moderate to severe hearing loss, retinitis pigmentosa (RP), and normal vestibular function. RP usually develops from the second decade onwards (Besnard et al, 2012; Chen et al, 2014). Early symptoms of RP include night blindness and loss of peripheral vision.…”
Section: Discussionmentioning
confidence: 99%
“…The PDZD7 mutation p.Arg56Profs*24 (c.166_167 insC) was suggested to be a retinal phenotype modifier in Usher syndrome in its heterozygous state. No biallelic mutations of PDZD7 were found in USH2 (Aparisi et al, 2014; Besnard et al, 2012). In this study, we did not find other functional candidate gene variants of classical Usher syndrome genes by targeted region capture and high throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%